EVALUASI PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMP CENDIKIA KECAMATAN LEMPUING KABUPATEN OKI TAHUN PELAJARAN 2021/2022 - Titin Toiyibah; Feri Riyansyah; Yuli Habibatul Imamah (UNISAN JURNAL, 2022)
The learning process is essentially a system of educational activities involving interrelated and influencing components. These are: raw input, namely students with all their psychological characteristics including motivation, interest, perception, activity, creativity and readiness to learn; instrumental input, includes everything, people or programs that are intentionally designed and formulated to create a learning process; environmental input includes environmental, social, cultural and physical factors that affect learning; The output consists of the goals or results to be achieved with the learning activities. This concept also applies specifically to PAI learning in Cendikia, Lemrub District, OKI Regency. Implementation of the PAI learning process in Cendikia, Lemembu Subdistrict. OKI Regency is running well and procedurally. However, there needs to be improvements in the implementation of apperception, the learning methods used, and the deepening and expansion and expansion of learning materials. Learning evaluation conducted by PAI teachers includes evaluation of learning processes and outcomes. Process evaluation is intended to assess and measure the level of effectiveness of the components of learning comprehensively. And the evaluation of results aims to measure the learning progress achieved by students after completing learning in one basic competency or several basic competencies. Keywords: Evaluation, PAI Learning Process